2011
DOI: 10.4028/www.scientific.net/amm.138-139.995
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Concentration of C-Phycocyanin from <i>Spirulina</i> <i>platensis</i> Using Aqueous Two-Phase System

Abstract: In this article, the partitioning behavior of C-phycocyanin (C-PC) in aqueous two-phase systems (ATPS) with different component was investigated to evaluate the applicability of ATPS for extracting high purity of C-PC without chromatography. Under the optimized conditions (pH = 6; PEG-2000, 16 %, w/w; potassium sodium tartrate 21 %, w/w), a maximum purity of 5.01 was achieved after the whole separation process and the yield of the C-PC was 76.94 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We also include a comparative study of these systems with those containing sodium citrate/tartrate, previously reported. Besides, a particular effort is focused in applying an extension of Pitzer model [14] for the excess Gibbs free energy of aqueous electrolyte solutions to describe and predict binodal curves and partitioning behaviour of model proteins, in an attempt to aid a rational design and optimization of aqueous two-phase extraction using these biodegradable salts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also include a comparative study of these systems with those containing sodium citrate/tartrate, previously reported. Besides, a particular effort is focused in applying an extension of Pitzer model [14] for the excess Gibbs free energy of aqueous electrolyte solutions to describe and predict binodal curves and partitioning behaviour of model proteins, in an attempt to aid a rational design and optimization of aqueous two-phase extraction using these biodegradable salts.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the use of ATPSs formed by PEG and sodium succinate, tartrate and citrate salts becomes attractive due to the biodegradability of these anions and therefore, their improved eco-friendly characteristics when compared to the traditional ATPSs. Previous works from other authors focused on the experimental description, modeling and application of certain PEG/citrate [11][12][13] and PEG/tartrate ATPSs [14]. In our laboratory, we further explored these systems in a systematic manner and reported complete (liquid + liquid) equilibrium data corresponding to ATPSs formed by sodium citrate/tartrate and PEGs of different molecular mass (600, 1000, 2000, 4000, 6000, and 8000) g Á mol À1 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The ATPS system, formed by [Emim]­[EtSO 4 ] (IL), K 2 HPO 4 (salt), and water, was prepared in 25 mL centrifuge glass tubes that contained the appropriate amounts of all the three components above. Before adding the crude extract into the ATPS system, the pH was adjusted to 6.5 using HCl (ACS reagent, 37%, Sigma-Aldrich) because PC is stable within the pH range 6.0–7.0 and starts degradation at pH values above 7. , Then, the ATPS system and the crude extract were mixed in a vortex for 1 min. The blend was centrifuged at 4000 rpm for 5 min to complete the separation of both phases.…”
Section: Methodsmentioning
confidence: 99%
“…Before adding the crude extract into the ATPS system, the pH was adjusted to 6.5 using HCl (ACS reagent, 37%, Sigma-Aldrich) because PC is stable within the pH range 6.0−7.0 and starts degradation at pH values above 7. 38,39 Then, the ATPS system and the crude extract were mixed in a vortex for 1 min. The blend was centrifuged at 4000 rpm for 5 min to complete the separation of both phases.…”
Section: Purification Approach 2: Atps + Dialysis +mentioning
confidence: 99%
“…seemed to be insufficient in some studies (entry 6) [74], even if salting out was associated with other purification techniques (entries 10 and 11) [75,76] with the aim of obtaining a high final purity. With a concentration of 39% to 50%, purity can be increased from 0.9 to 1.3 (entry 4) or from 1.8 to 2.2 (entries 6-8) [28,74].…”
Section: Purification By Salting Outmentioning
confidence: 99%